TRADISI HAFLAH DI PONDOK PESANTREN AL ASY'ARIYAH WONOSOBO: INTEGRASI BUDAYA LOKAL DAN KEGIATAN KEISLAMAN - Lia Amalia; Adi Prasetyo (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2025)
The Haflah Khotmil Qur’an (HKQ) at Pondok Pesantren Tahfidzul Qur’an Al Asy’ariyyah in Wonosobo embodies a religious custom blending Islamic principles, local traditions, and community care. This research describes the haflah's execution and uncovers its religious, social, and cultural significance. Adopting a descriptive qualitative method, data were gathered via observation, interviews, and documentation, with informants chosen through purposive and snowball sampling. Results indicate HKQ extends beyond celebrating students' Qur’an memorization achievements, acting as a platform for Islamic outreach and fostering ties between the pesantren and local society. Diverse events—including santri contests, napak tilas treks, grave visits, Hamalatul Qur’an, communal recitations, blood drives, and mass circumcisions—highlight the fusion of spiritual piety and social commitment. This practice is vital for upholding moderate Islam, bolstering students' faith identity, and preserving indigenous values against modernization pressures